Much ado about Chopin. Discussion in the Warsaw press from 1830 - Strzyżewski, Mirosław (Interdisciplinary Studies in Musicology, 2018)
During his Warsaw period, the music of the young Chopin was enthusiastically and even feverishly received. And it drew considerably interest from the critics. However, attention should be drawn to the crucial cultural factors that largely determined the quality of that critical reflection. Above all, this was a quite specific period in the history of the nation. The language o f criticism gives a fair reflection of moods in the country: growing patriotic emotions, freedom rhetoric and Romantic spirituality. Added to this, Polish music criticism (in contrast to German criticism) had yet to develop distinctive forms of discourse, but was still seeking a suitable language for the description of music. One may even gain the impression that music criticism was maturing together with the young virtuoso and offering a “youthful” discourse strung out between literary metaphor depicting the scale of listeners’ emotions and impressions and specialist description of playing and composition technique. One also notes a growing tension between “amateurs” and “professionals”, leading to polemic and discussion. It was a most interesting period in the history of Polish critical reflection, one which obliges the scholar to maintain a broad humanistic perspective over the many cultural phenomena of that time (philosophical, literary, artistic and political) which helped to forge the spirituality of Polish romanticism.